A miniaturized circularly polarized multi‐dipole antenna with wide axial‐ratio beamwidth via loading loop resonators. Issue 9 (22nd May 2020) - Zheng, Dongze; Luo, Yu; Chu, Qing‐Xin
Abstract: A miniaturized, loop resonators (LRs)‐loaded, circularly polarized (CP) multi‐dipole antenna with wide axial‐ratio (AR) beamwidth is proposed and demonstrated in this article. The radiator of this CP antenna consists of two pairs of parallel dipoles loaded with four LRs at their corners. By increasing the length of the LR, or decreasing the coupling space between the dipole and the LR, the effective length of the dipole can be lengthened significantly and thus the working frequency can be reduced without increasing the whole aperture size. As a result, a miniaturized radiator structure is completed. A feeding network consisting of a T‐shaped coupling feeding structure and four coplanar striplines having different lengths are specially designed to feed these dipoles with approximately the same magnitude and 90° phase quadrature. What is more, a cavity reflector is employed to achieve a unidirectional radiation with wide axial‐ratio beamwidth. The radiator of the proposed CP antenna has a small aperture size of only 0.34 λ 0  × 0.34 λ 0, where λ 0 is the free space wavelength at the working frequency. Measured results are in a good agreement with the corresponding simulated counterparts. Especially, the experimental results show that the antenna has achieved a wide AR beamwidth of 182° and 174° at the center frequency in the xoz and yoz planes, respectively.